2023
DOI: 10.1002/smsc.202300068
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Photosynaptic and Electrical Memory Functions in Organic Nano‐Floating‐Gate Transistors via a Perovskite‐Nanocrystal‐Based Nanocomposite Tunneling Layer

Abstract: An organic nano‐floating‐gate transistor (ONFGT) with both photosynaptic and electrical memory functions is developed using a perovskite (CsPbBr3) NC‐insulating polymer (polystyrene; PS) nanocomposite and CsPbBr3 NCs as the tunneling and floating gate layers, respectively. The introduction of the CsPbBr3 NCs–PS nanocomposite layer improves the photoresponsivity of the ONFGT under ultraviolet–visible irradiation, resulting in an increase in both the photocurrent and the light‐to‐dark current ratio by 10−8 A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…5(a), Moon et al employed a PS-CsPbBrNCs nanocomposite and CsPbBrNCs as the tunnel layer and floating gate layer, respectively, to create an organic nano-floating-gate transistor featuring both visual synaptic and electrical storage functionalities. 118 As shown in Fig. 5(b) and (c), ONFGT reached dynamic modulation of synaptic weight by adjusting the intensity and duration of ultraviolet light.…”
Section: Organic Artificial Synapsementioning
confidence: 83%
See 1 more Smart Citation
“…5(a), Moon et al employed a PS-CsPbBrNCs nanocomposite and CsPbBrNCs as the tunnel layer and floating gate layer, respectively, to create an organic nano-floating-gate transistor featuring both visual synaptic and electrical storage functionalities. 118 As shown in Fig. 5(b) and (c), ONFGT reached dynamic modulation of synaptic weight by adjusting the intensity and duration of ultraviolet light.…”
Section: Organic Artificial Synapsementioning
confidence: 83%
“…5(b) and (c), ONFGT reached dynamic modulation of synaptic weight by adjusting the intensity and duration of ultraviolet light. 118 As shown in Fig. 5(d), Chen et al reported a high-performance electrically stimulated long afterglow organic light-emitting transistor with a nano floating gate structure.…”
Section: Organic Artificial Synapsementioning
confidence: 96%